An Empirical Study on the Impact of Consumer Engagement in Value Co-creation —— An Example of the Apparel Industry in China - MU, Yutong (2022)
The essence of a company is value creation, and with the advent of the Internet economy, co-creation of value between companies and consumers has become the basis of corporate value creation. With the rapid development of the Internet, information is more easily and quickly accessible, which has rapidly increased the ability of consumers to learn, and has given them the ability and maturity to participate in the value co- creation of companies. Consumer participation in value co-creation benefits not only companies but also consumers themselves. Therefore, research on the impact of consumer participation on value co-creation is an important research topic. This paper explores the impact of consumer participation on value co- creation by combing through the relevant theoretical literatures and adopting the Chinese apparel industry as the sample for this study. The paper analyses the factors affecting consumer participation in terms of both consumer and company dimensions, segmenting consumer participation in value co-creation activities into consumer willingness to participate, consumer ability to participate and company openness, and exploring their impact on consumer participation behaviour. The specific research questions are as follows, in the context of consumer participation in value co-creation: First: How do consumers' willingness to participate affect participation behaviour? Second: How does the consumer's ability to participate affect participation behaviour? Thirdly: How does the openness of the company affect the consumer's participation behaviour? In terms of data collection, this paper collects primary data by designing a questionnaire and using SPSS24.0 statistical software to analyse and process the 520 valid data collected. The empirical findings show that consumer willingness to engage, consumer ability to engage and the openness of companies are all significantly and positively related to consumer engagement behaviour. Finally, based on the findings of this paper, reasonable suggestions are made for business practice strategies. Possible directions for future research are suggested to address the limitations and shortcomings of this paper.